Hello!
We have the function f(x) = 3x.
The first step is to calculate the inverse function of f(x):
First, let's replace where's f(x) by y:
f(x) = 3x
y = 3x
Now, let's swap the values of x and y:
y = 3x
x = 3y
Now we have to solve it to obtain y:
3y = x
y = x/3
So, we will have:
![f(x)^(-1)=(x)/(3)](https://img.qammunity.org/2023/formulas/mathematics/college/2udgjt3hhnlg1f0jmc2t306bhtxp0zdvr1.png)
B. Reasoning:
![\begin{gathered} f(f^(-1)(x))=(3((x)/(3))=x \\ \\ f^(-1)(f(x))=(3x)/(3)=x \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/cl2oqv7xqhl305uu50hl8x2l0z01ozfwfc.png)
Image with the reasoning:
So, these equations are correct.
As it has no restrictions, this function is valid for all values of x.
Right answer: alternative A.
Obs: You'll have to type in the first box: x/3.